Dietary Supplementation of an Organic Acid-Based Feed Attractant in Juvenile Largemouth Bass (Micropterus salmoides): Effects on Growth, Morphohistology, and Oxidative Stress - Guohe Cai; Zhizhong Li; Miao Yu; Mingya Huang; Pengao Liu; Xiudan Tang; Qizhe Huang; Zhixue Guo; Yunzhang Sun (Fishes)
Aquaculture plays a crucial role in China’s agricultural sector, with improved growth performance and feed efficiency in cultured species representing key industry challenges. Among nutritional strategies, feed attractants have received increasing attention for their ability to stimulate feeding behavior and enhance feed utilization. This study hypothesized that dietary supplementation with a formulated feed attractant would enhance feeding activity, improve physiological condition, and modulate antioxidant and immune responses in juvenile largemouth bass (Micropterus salmoides). A total of 270 fish (initial weight: 12.5 ± 2.5 g) were randomly assigned to three groups: CON (basal diet), YXX0.05 (basal diet + 0.05% attractant), and YXX0.1 (basal diet + 0.10% attractant). After 56 days of feeding, no significant differences were observed in final body weight (FBW) or whole-body composition (p > 0.05). However, feed intake (FI) increased by 5.1%, and the condition factor (CF) improved significantly by 7.6% (p < 0.05) in the YXX0.05 group, while the viscerosomatic index (VSI) was reduced by 3.6% (p < 0.05), suggesting enhanced feeding motivation and improved body compactness. In terms of physiological responses, compared to the control group, the YXX0.05 group exhibited a significant increase in liver total antioxidant capacity (T-AOC) (p < 0.05), a significant decrease in malondialdehyde (MDA) content (p < 0.05), an increase in serum lysozyme (LZM) activity (p < 0.05), and a significant decrease in aspartate aminotransferase (AST) activity (p < 0.05), reflecting enhanced immune status and potential liver protection. In conclusion, although growth performance metrics such as FBW and specific growth rate (SGR) remained unchanged, the feed attractant at 0.05% inclusion significantly improved feed intake, body condition, and physiological health markers. These results suggest the attractant has practical value in improving fish welfare and nutrient utilization efficiency, providing a functional dietary strategy for sustainable largemouth bass farming.